Education in the Arab world - Kirdar, Serra 1975- (Education around the world series, 2017)
This is a critical reference guide to development of education in Iraq, Jordan, Lebanon, Palestine, Syria, Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, the United Arab Emirates, Yemen, Algeria, Egypt, Libya, Morocco, Sudan and Tunisia. The chapters, written by local experts, provide an overview of the education system in each country, as well as discussion of educational reforms and socio-economic and political issues. Including a comparative introduction to the issues facing education in the region as a whole and guides to available online datasets, this book is an essential reference for researchers, scholars, international agencies and policy-makers.